Attitude toward the Viral Ad: Expanding Traditional Advertising Models to Interactive Advertising. Issue 1 (February 2013) - Huang, Jinsong; Su, Song; Zhou, Liuning; Liu, Xi
As a form of advertising, viral video (VV) advertising is distinct in that its communication medium is the social connections between individuals instead of formal media. After viewing VV advertising, people are engaged in two independent but interrelated processes, i.e., video sharing and embedded brand information processing. Previous research has not examined the interaction between the two processes. This study expands on the mediation of attitude toward the advertisement model proposed by MacKenzie, Lutz, and Belch (1986). Experimental results from three viral video advertisements show that attitude toward the VV advertisement is the major factor affecting video sharing, but attitude toward the brand also has a significant impact on sharing activity. Affect transfer hypothesis (ATH) and its extended models are optimal in explaining viral video advertising, which is different from prior research on non-viral advertising that suggests dual mediation hypothesis as the optimal explanatory theory.